Evasive Actions: The gendered cycle of stress and coping for those enduing workplace bullying in American higher education - Hollis, Leah (Advances in Social Sciences Research Journal, 2017)
Previous studies have confirmed that American higher education professionals endure workplace bullying at a rate higher than the general population. Close to two-thirds of American higher education employees were affected by workplace bullying and often endure the bullying at least two to three years. While the frequency of workplace bullying has been examined, along with the corresponding cost of employee disengagement, an analysis of how higher education employees cope with the stress of workplace bullying is absent from the literature. Within the theoretical stress and coping frameworks, this essay examined how higher educational personnel cope with stressful workplace bullying. A chi-square analysis was utilized on a sample (n=355) of American higher education respondents to determine the difference of the gender for respondents’ reactions. The chi-square analysis showed that women were more likely to quit/resign from a job in reaction to workplace bullying, and men are more likely to take more sick time in response to workplace bullying.